ASPEK FISIKA DAN MEKANIKA TANAH ASOSIASI REGOSOL BANJARWANGI KABUPATEN GARUT - Mustafril Mustafril (Jurnal Agrista, 2003)
Development of terraces which is applied for soil and water conservation often experiences failure with occurance of sliding, like several agricultural lands in sub district of Banjarwangi, Garut Regency. Slide at farm of bench terrace is influenced by soil physics and mechanics properties. For that purpose it requires to conduct research of soil and mechanics properties in the area of gristle slide. Result of inspection is physical properties of Regosol Association soil within two condition, that is undisturbed and compacted condition. The result shows as follows the average water content is 47.82 % and 28.83 % respectively. The average porosity is 68.30 % and 53.54 % and the average permeability is 5.89 mm/jam and 0.69 mm/jam, respectively. Soil texture is silt loam. The result of proctor test that is maximum densities is 1.40 t/m 3 and the optimum water content is 28.83 %. Inspection of soil mechanic properties with triaxial test shows that at the mean density of 1.44 t/m 3. The effective cohesion is on average 0.15 kgf/cm2 and the internal friction angle average is 20.3 for natural condition. If soil is compacted with optimum water content, it shows improvement on strength with the average density is 1.732 t/m3, the average effective cohesion is 0.722 kgf/cm2, and the average internal friction angle is 28. 48 . The maximum shear strength of soil increases if optimum water content applied.